A COMPARATIVE STUDY FOR SEED EXTRACTION METHODS : AIR BLOWERING AND WATER SOAKING FOR TWO ONION VARIETIES - Mohammad Al-Habar (Mesopotamia Journal of Agriculture)
A comparative study was done to evaluate quantitative efficiency of two methods for seed extraction: air blowering and water soaking of two onion varieties (Local White and Imported Texax Early Grano), and two methods for seeds extraction from a residual product resulted from the two previous methods i.e. water soaking to the residual product produced by air blowering and air blowering to the residual product produced by water soaking. Also the aims of this study is to evaluate seed viability and seed vigour of the extracted seeds. The results indicated that air blowering method was significantly superior in seeds weight and percentage of the extracted seeds, whereas, water soaking method gave the best results in seed purity percentage, seed index, true value of the extracted seeds and also seed viability and seedling vigour characters i.e. seedling and root length, fresh and dry weight of the seedling. The results also showed that the seeds resulted by water soaking from the residual product  by air blowering were ineffective as it gave a low weight of extracted seeds(2.53 %) and low viability and seedling vigour, whereas, the seeds resulted by air blowering from the residual product by water soaking gave a hight weight of extracted seeds (36.29 %)and a good quantity and quality of seed viability and vigour. The imported variety (Texax Early Grano) was superior than the local white variety in all traits of above mention studied.